Contrast training in football and its effect on the performance of students in this field of education - Korkmaz, Sezgin (2021)
Many factors determine success in football. But the most important of these are the physical and physiological variables that determine the performance of football players. Meeting these physical and physiological needs is also based on training methods prepared following branch-specific neural, muscular, and metabolic parameters. In football, for some reason, sufficient time cannot be allocated to the biomotor properties that need to be developed. Different methods are put forward to eliminate the obstacles that occur. One of these methods, which was discussed in the educational system of this field, was the idea of combining different strength training. Although there are different designs on these training in the literature, the most commonly studied methods are complex and contrast training. Complex and contrast training is based on the theory of post-activation potentiation, although there are minor differences between them. These methods generally include plyometric exercise followed by a severe strength exercise. For this reason, contrast and complex training are considered by some researchers as similar training methods, while studies that claim otherwise are also found in the literature. Discussions continue in terms of training protocols and training terms which are used. These methods are investigated by experts with many different protocols when the literature is examined. Confusion in the literature also affects studies on football. Complex and contrast training protocols in football that are used to define the purpose of this study, to examine the effect on player performance, on methods to deal with developments and discussions with existing methods to evaluate the positive and negative aspects to provide a critical perspective on sensible recommendations.